Calibration of Local Magnitude Scales for use in Seismic Monitoring - Murphy, J. R.; Marshall, M. E.; Barker, B. W.; Bennett, T. J.; Rivers, W. (1995)
In situations where cavity decoupling is a plausible evasion scenario, comprehensive monitoring of any eventual CTBT will require the routine identification of many small seismic events with magnitudes in the range 2.0 < mb < 3.5. Thus, an important issue in the assessment of monitoring requirements concerns the definition of the numbers and types of events which will generate seismic signals in this magnitude range. This has proved to be a difficult question to answer with any real degree of confidence, because the magnitude values reported for most small events are based on a variety of regional magnitude scales which may not be consistent with the teleseismic mb magnitude scale which is used to specify seismic monitoring capability. Under this project, we are attempting to quantitatively relate such regional magnitude measures to mb. This is being accomplished by theoretically scaling observed regional seismic data recorded from tamped underground nuclear tests to obtain estimates of the corresponding seismic signals to be expected from small cavity decoupled nuclear explosions at those same source locations. These synthetic data are processed to determine various local magnitude measures which can then be directly correlated with the known mb values of these synthetic explosions. This theoretical scaling procedure has now been applied to regional seismic data recorded at the Scandinavian NORESS and ARCESS arrays from tamped Soviet nuclear explosions at the Novaya Zemlya and selected PNE sites and to data recorded at IRIS stations from explosions at the Semipalatinsk and Lop Nor test sites. Results of analyses of these synthetic data indicate that, even for the well-calibrated Scandinavian arrays, regional magnitude measures can show a pronounced dependence on source location and type. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p252-261.